Peritransplant predictors of small-for-size syndrome and surveillance of graft functions in an Egyptian Adult Living Donor Liver Transplantation Center. Issue 3 (July 2017) - Riad, George S.; Hussein, Hany A.; Kaisar, Hany H.; Bahaa, Mohammed; Fathy, Mohammed; El-Meteini, Mahmoud
Abstract : Background and aim: Small-for-size syndrome (SFSS), which is characterized by synthetic dysfunction and prolonged cholestasis, is a major cause of worse short-term prognosis after adult living donor liver transplantation (ALDLT). It is true that a number of donor and recipient factors other than the graft volume, such as donor age, status of parenchymal quality, and preoperative status of the recipient, influence the graft functionality. The main aim of this study was to predict potential peritransplant factors that lead to portal hyperperfusion and small-for-size grafts which result in small-for-size syndrome in ALDLT. Patients and methods: This study was conducted on 45 Egyptian adult recipients and their graft donors in one of Egyptian ALDLT Center. The recipients were divided as follows: group I: included eight recipients diagnosed as SFSS. This group was subdivided into two subgroups according to mortality incidence. Subgroup 1A: included five recipients who are still alive. Subgroup 1B: included three recipients, two of them died after 21 days, and the third one died after 1 month. Group II: included 37 recipients without SFSS. Perioperative predictors of SFSS in both recipients and donors were assessed and compared between the two groups. Results: Graft volume recipient weight ratio (GRWR) was the only recipient's preoperative parameter showing significant difference between the two groups. In comparison between recipients with GRWR of less than 0.8 and recipients with GRWR of more than 0.8, there was significant difference between them as regards splenic artery ligation ( P <0.05). In comparison between two subgroups of group I [group A (five living recipients) and group B (three dead recipients)], the donor age had significant difference between the two subgroups ( P <0.05). Conclusion: GRWR can be used as a predictive valuable tool for SFSS development in right lobe grafts in Egyptian patients undergoing ALDLT. Donor age had a significant effect on the outcome of SFSS.